STUDY OF QUALITY OF DRY SKIN SHRIMP (Acetes arythraeus) SAUCE WITH DIFFERENT FERMENTATION TIME AND SALT CONCENTRATION - Rizki Syakbana Nasution; Suparmi Suparmi; Dahlia Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT     The purpose of this study was to determine the quality of dry skin shrimp (Acetes arythraeus) sauce with different fermentation time and salt concentration. The treatment was fermentation time (L): 20 days (L1), 30 days (L2) and 40 days (L3), and different salt concentration (G) 15% (G1), 20% (G2), and 25% (G3). The results showed that the addition of different salt concentration and fermentation time to the production of dry skin shrimp sauce had a very significant effect on taste and aroma values. L2G2treatment was the best treatment with characteristics ofaroma was specific of dry skin shrimp,the taste of the spices was specific and felt salt and dry skin shrimp, meanwhile for the color was no effect at all. The contained of proximate values of protein, ash, and amino acids were 10.54%, 18.26% and4.92%, respectively.Meanwhile fat content was no significant effect.Keywords: dry skin shrimp sauce, fermentation time, quality.